The Negative Impact of Social Media on the Morals of Teenagers in the Al Falah Mosque Environment - Lutfanudin; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to reveal the adverse effects of social media use on the morals of adolescents around Al Falah Mosque, Sragen, and develop strategies to reduce these negative influences. The mosque in this case has a function as a center for Islamic moral and character development, which currently faces great challenges from the influence of social media. The research was conducted with a qualitative approach using the case study method. Data collection was conducted through in-depth interviews with mosque administrators, active teenagers, and their parents, coupled with direct observation of activities at the mosque. In addition, documentation from various sources was used to expand the information and ensure the accuracy of the findings. The results indicate that social media has significant negative impacts, such as increased addiction to online gambling, weakened social relationships, and low involvement of teenagers in mosque activities. The main influencing factors include lack of parental supervision and lack of education on the wise use of social media. The findings emphasize the important role of mosques, families and communities in providing guidance to teenagers to make positive use of social media. This study recommends the implementation of educational programs on the ethical use of social media in mosques as well as strengthening teenagers' involvement in religious activities to form a stronger Islamic character.